Semiotic Meaning and Strategic Purpose of Vista Lima - Perusset, Alain (2023)
The COVID crisis in 2020 deeply impacted world economy. Peru, which had a booming tourism sector, suffered severely from the fall in international arrivals to its territory. To reactivate local economy, the Municipality of Lima launched, at the end of 2020, a digital magazine called Visita Lima. The aim of this article is to show how a postgreimasian semiotic analysis can provide a critical look at the offering of a brand. In this case, the different digital channels of Visita Lima will be analyzed in order to highlight some strategic issues and to propose solutions to make such an offering more relevant and meaningful.